THE LEVEL OF FAMILY CAREGIVERS INVOLVEMENT AND QUALITY OF LIFE IN CARING FOR CANCER PATIENTS AT WAHIDIN SUDIROHUSODO HOSPITAL MAKASAR - Rahmatiah Rahmatiah; Kusrini Kadar; Kadek Ayu Erika (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Background: cancer is one of the causes of morbidity and mortality around the world. The involvement of family members taking the role as caregivers in care is important. This study aims to describe the level of involvement and the quality of life of family caregivers in caring for cancer patients at the hospital. Methods: this research using quantitative methods with cross-sectional approach as much as 133 samples from the family of a cancer patient who was in RSUP. Wahidin Sudirohusodo in July 2018. The data collected to obtain an overview of sosiodemografi, engagement and quality of life of family caregivers using the Family Caregivers Involvement in Caring-Cancer (FCIC-C) and Caregiver QoL Index-Cancer (CQOLC) questionnaire. Results: the level of involvement of family caregivers toward cancer patients high (mean = 52.07; SD ± 14.01), where the domain of involvement in psychological issues is the highest order (mean = 9.51; SD ± 5.37). But quality of life is a little low (mean = 71.22; SD ± 21.33). Conclusion: Involvement of family caregivers in caring for cancer patients in RSUP. Wahidin Sudirohusodo is high especially in the domain of the fulfillment of psychological issues and social problems of patients but on the quality of life of life family caregivers a bit downhill.